Pb(core)/ZnO(shell) nanowires obtained by microwave-assisted method - Solís Pomar, Francisco; Meléndrez, Manuel F.; Esparza, Rodrigo; Pérez Tijerina, Eduardo (Springer, 2011)
In this study, Pb-filled ZnO nanowires [Pb(core)/ZnO(shell)] were synthesized by a simple and novel one-step vapor transport and condensation method by microwave-assisted decomposition of zinc ferrite. The synthesis was performed using a conventional oven at 1000 W and 5 min of treatment. After synthesis, a spongy white cottonlike material was obtained in the condensation zone of the reaction system. HRTEM analysis revealed that product consists of a Pb-(core) with (fcc) cubic structure that preferentially grows in the [111] direction and a hexagonal wurtzite ZnO-(Shell) that grows in the [001] direction. Nanowire length was more than 5 μm and a statistical analysis determined that the shell and core diameters were 21.00 ± 3.00 and 4.00 ± 1.00 nm, respectively. Experimental, structural details, and synthesis mechanism are discussed in this study